PENGARUH GOOD CORPORATE GOVERNANCE DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA PERUSAHAAN - Tati Rosyati; Fina Fitriyana (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2022)
Abstract This study aims to examine the effect of independent commissioners, managerial ownership, and audit committees on firm value with audit quality as a moderating variable. The population in this study are all companies that are members of the 2016-2020 LQ45 index. The number of samples in this study was 12 companies obtained by purposive sampling method. Obtained sample data as much as 60 data. The type of data in this study is secondary data with quantitative research methods and descriptive approaches. The analysis technique used is multiple linear regression analysis and moderated regression analysis with a significance level of 5%. This research is processed using the software eviews 9 and shows that independent commissioners affect firm value, managerial ownership affects firm value, audit committees have no effect on firm value, independent commissioners, managerial ownership, and the audit committee has an effect on firm value, audit quality is unable to moderate the influence of independent commissioners on firm value, audit quality can moderate managerial ownership on firm value, audit quality is unable to moderate the audit committee on firm value, audit quality can moderate the influence of independent commissioners, managerial ownership, and audit committees on firm value.